2018
DOI: 10.1016/j.aquatox.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Role of mTOR in autophagic and lysosomal reactions to environmental stressors in molluscs

Abstract: Lysosomal membrane stability (LMS) has been used in various organisms as a very sensitive biomarker of stress. However, despite the abundance of data about regulation of the autophagic process in mammals, in the invertebrates there is only limited mechanistic understanding. Marine mussels (Mytilus galloprovincialis Lam.) are bivalve molluscs, widely used as models in ecotoxicology and as environmental bioindicators of sea water quality. In order to elucidate this fundamental process, in the present study, muss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 86 publications
2
57
0
1
Order By: Relevance
“…Thus, CMA can be designated a stress-induced pathway that is activated not only by nutrient deprivation but also by mild oxidative stress 44 and exposure to toxic compounds. 14,21,31 This was clearly demonstrated by Massey et al 45 who impaired CMA in mouse cells. The survival rates of these cells were unaffected when maintained under optimum conditions and it was hypothesized that the cells were able to upregulate macro-and microautophagic pathways to sustain protein turnover homeostasis.…”
Section: Hormeɵc Effect Of Lysosomal Autophagymentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, CMA can be designated a stress-induced pathway that is activated not only by nutrient deprivation but also by mild oxidative stress 44 and exposure to toxic compounds. 14,21,31 This was clearly demonstrated by Massey et al 45 who impaired CMA in mouse cells. The survival rates of these cells were unaffected when maintained under optimum conditions and it was hypothesized that the cells were able to upregulate macro-and microautophagic pathways to sustain protein turnover homeostasis.…”
Section: Hormeɵc Effect Of Lysosomal Autophagymentioning
confidence: 90%
“…Increasing stress resulted in a decline in connectance, indicative of a loss of complexity and increasing cell injury. 21,29,30 Connectivity associated with autophagy was a significant factor in the increase in connectance induced by mild stress. The outputs from this simulation have since been validated in experimental studies with molluscan hepatopancreas or digestive gland.…”
Section: Introductionmentioning
confidence: 96%
“…Mollusk bivalves are generally exposed to numerous biotic (pathogens) and abiotic (tide, pollution) stressors. Initial studies demonstrated that the autophagy pathway can play an important role in the response to these different stress factors [12,[15][16][17], highlighting the importance of elucidating the autophagy pathway in bivalve mollusks. In this study, we identified the autophagy pathway by data mining of the Pacific oyster genome [14].…”
Section: Discussionmentioning
confidence: 99%
“…These results may indicate an alteration in the growth of mussels in this area in particular and in highly polluted zones in general. The LMS correlates with the scope for growth (Moore et al, 2006); LMS is now considered in different model organisms to be a prognostic biomarker capable of providing early evidence of future noxious consequences at the population level (Moore et al, 2006;Sforzini et al, 2018).A possible interpretation of these results involves the role of mechanistic target of rapamycin (mTOR), a key element in the regulation of autophagy, protein synthesis, and energy metabolism (Antikainen et al, 2017). In mussels exposed to toxic chemicals, the level of the phosphorylated active form of mTOR was recently demonstrated to decrease strongly; in the same animals, a drastic increase in autophagy was observed (Sforzini et al,2018).…”
Section: Discussionmentioning
confidence: 99%